Tracheal Macrophages During Regeneration and Repair of Long‐Segment Airway Defects. (21st June 2021) - Tan, Zheng Hong; Dharmadhikari, Sayali; Liu, Lumei; Wolter, Gabrielle; Shontz, Kimberly M.; Reynolds, Susan D.; Johnson, Jed; Breuer, Christopher K.; Chiang, Tendy
Abstract : Objectives/Hypothesis: Tissue‐engineered tracheal grafts (TETGs) offer a potential solution for repair of long‐segment airway defects. However, preclinical and clinical TETGs have been associated with chronic inflammation and macrophage infiltration. Macrophages express great phenotypic heterogeneity (generally characterized as classically activated [M1] vs. alternatively activated [M2]) and can influence tracheal repair and regeneration. We quantified and characterized infiltrating host macrophages using mouse microsurgical tracheal replacement models. Study Design: Translational research, animal model. Methods: We assessed macrophage infiltration and phenotype in animals implanted with syngeneic tracheal grafts, synthetic TETGs, or partially decellularized tracheal scaffolds (DTSs). Results: Macrophage infiltration was observed following tracheal replacement with syngeneic trachea. Both M1 and M2 macrophages were present in native trachea and increased during early tracheal repair ( P  = .014), with an M1/M2 ratio of 0.48 ± 0.15. In contrast, orthotopic implantation of synthetic TETGs resulted in a shift to M1 predominant macrophage phenotype with an increased M1/M2 ratio of 1.35 ± 0.41 by 6 weeks following implant ( P  = .035). Modulation of the synthetic scaffold with the addition of polyglycolic acid (PGA) resulted in a reduction of M1/M2 ratio due to an increase in M2 macrophages ( P  = .006). Using systemic macrophage depletion, the M1/M2 ratio reverted to native values in synthetic TETG recipients and was associated with an increase in graft epithelialization. Macrophage ratios seen in DTSs were similar to native values. Conclusions: M1 and M2 macrophages are present during tracheal repair. Poor epithelialization with synthetic TETG is associated with an elevation of the M1/M2 ratio. Macrophage phenotype can be altered with scaffold composition and host‐directed systemic therapies. DTSs exhibit M1/M2 ratios similar to those seen in native trachea and syngeneic tracheal replacement. Level of Evidence: NA Laryngoscope, 132:737–746, 2022